Managing The Merdeka Curriculum Through The P5-PPRA Project On Entrepreneurship At MTsN 1 Jombang - Athiya Nur Nabila; Nur ‘Azah; Abdullah Aminuddin Aziz (Pondok pesantren As-salafiyah As-Safi'iyyah, 2025)
The purpose of this study is to examine the implementation of Merdeka Curriculum management in the Pancasila Student Profile Strengthening Project and Rahmatan lil Alamin Student Profile (P5-PPRA) with an entrepreneurial theme at MTsN 1 Jombang. This qualitative research employs a descriptive case study method to explore curriculum management across three key stages: planning, implementation, and evaluation. The findings reveal that the planning phase involves forming a facilitator team, developing project modules, and selecting relevant themes. During implementation, students are actively engaged in producing and marketing traditional food, thereby enhancing entrepreneurial skills and internalizing character values aligned with Pancasila and Rahmatan lil Alamin principles. The evaluation process is reflective and comprehensive, assessing both learning outcomes and character development. The program's success is attributed to strong collaboration among stakeholders, adequate facilities, and a culture of cooperation within the madrasah. These results suggest that flexible, inclusive, and sustainable curriculum management plays a vital role in responding to modern educational challenges. The study offers valuable insights that can guide other madrasahs and education policymakers in effectively applying project-based learning for character and competency development.